Analisis Value For Money Dalam Menilai Kinerja Keuangan Pada Badan Keuangan Daerah Kota Kupang - Maria Selina Dhoe; R. Setyo Budi Suharto; Yunelci M. Seliamang (JAKA - Jurnal Jurusan Akuntasi, 2019)
The increasing of public awareness toward the implementation of the public administration, the performance of government agencies now is become the spotlight. The public sector organizations were often seen as a den of inefficiency, dissipation, sources of leakageof funds and the institutions that are always suffer losses. An increasingly intelligent and critical society demands that public sector institutions and transparency be carried out in order to create good governance. In fact, the budget and realization of the Badan Keuangan Daerah Kota Kupang still does not appropriate yet with the targets achieved. The purpose of this study was to determine the financial performance of the Badan Keuangan Daerah Kota Kupang through value for money analysis.The data collection method used is documentation, with the object of research being the target report and the realization of the budget of the Badan Keuangan Daerah Kota Kupang in the period of 2016-2018. The data analysis technique used is quantitative analysis on economic, efficiency and effectiveness measurements.The results of the research on the financial performance of the Badan Keauangan Daerah Kota Kupang from the economic element of the Badan Keuangan Daerah Kota Kupang was categorized as quite economical because it was in the ratio between 85%-100%. From the efficiency element, the Badan Keuangan Daerah Kota Kupang in 2016 was in the inefficient category because the efficiency ratio showed more than100%. Whereas in 2017 and 2018 were categorized as efficient because the results of the efficiency ratio showed between 90%-99%. From the effectiveness element of financial performance in 2016-2018, was categorized s quite effective because the level of effectiveness ratio was between 85%-99%.